Intervenções eficazes na prevenção ou redução da sobrecarga do familiar cuidador: revisão sistemática da literatura - França, Daniela; Peixoto, Maria José; Araújo, F. (Ediciones ROL, 2020)
The family caregiver role is highly demanding and very likely to trigger burden. A systematic literature review was conducted in order to identify effective interventions for the prevention/ reduction of the family caregiver burden. A search was conducted in SCOPUS, Web of Science and EBSCO databases from 2006 to 2016. Ten studies were selected involving different interventions (educational, psychoeducational, psycho-social and psycho-socio-educational). Despite the positive results of the different types of approach, the educational and multicomponent programmes revealed the most favorable outcomes. Considering the methodological heterogeneity observed, multi-center, longitudinal, prospective, controlled and mixed methodology studies should be carried out, leading to high-quality evidence-based results.
Effective interventions for the prevention and reduction of the family caregiver burden: a systematic literature review
Keywords: Family caregiver; Nursing Interventions; Burden; Efficacy